2001
DOI: 10.1046/j.1365-2265.2001.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin concentrations are associated with bone mineral density and the presence of vertebral fractures in postmenopausal women

Abstract: Our study showed that plasma leptin levels but not %fat are associated with BMD and the presence of vertebral fractures in postmenopausal women, suggesting that circulating leptin might play a physiological role in maintaining bone mass as well as better bone quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
120
1
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(131 citation statements)
references
References 29 publications
2
120
1
8
Order By: Relevance
“…This relationship was observed even in young patients with recent onset type 1 diabetes, leading to the hypothesis that insulin is a cornerstone of bone anabolic factor 28) . Also, Streptozocin-induced diabetic , while some showed negative correlations 19,20) . Likewise, consensus on the leptin-BMD relationship is not achieved in diabetic patients.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This relationship was observed even in young patients with recent onset type 1 diabetes, leading to the hypothesis that insulin is a cornerstone of bone anabolic factor 28) . Also, Streptozocin-induced diabetic , while some showed negative correlations 19,20) . Likewise, consensus on the leptin-BMD relationship is not achieved in diabetic patients.…”
Section: Resultsmentioning
confidence: 98%
“…More recent clinical trial showed that plasma leptin levels are associated with BMD and the presence of vertebral fractures in postmenopausal women 19) .…”
Section: Introductionmentioning
confidence: 99%
“…There are studies where a positive association has been found between leptin and BMD (14,23) while there are also studies reporting no significant association (8,24) or a negative association (13,25) Yamauchi et al (26) claimed that there is a relation between low plasma leptin levels and vertebral fractures in postmenapousal women and thus circulating leptin might play a physiological role in improving bone mass quality. Unsurprisingly, insulin values of the patients were significantly higher than controls, independent of gender.…”
Section: Discussionmentioning
confidence: 99%
“…These favorable bone effects also were observed in vivo because leptin administration increased bone mass in estrogen-deficient rodents, (30) and circulating leptin was positively associated with bone mass in pre-and postmenopausal women. (31)(32)(33) The relative contribution of leptin-mediated secretion of FGF-23 and renal handling of 1,25(OH) 2 D 3 and phosphate in the overall effects of leptin on bone is yet unclear but probably represents only a small part of the overall picture. Indeed, we still do not understand the mechanistic processes that positively link overweight (not true obesity) with bone mass and reduced fracture risk.…”
mentioning
confidence: 99%